International Conference on Livestock Agriculture in West and Central Africa: Achievements in the past 25 years, challenges ahead and the way forward - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
This conference aimed of answering to a strong demand for clarifications and prospective considerations on current concerns and stakes that characterise the livestock sector development in West & Central Africa.